Treatment-resistant prurigo nodularis - Kolli SS; Haidari W; Feldman SR (Dove Medical Press, 2019)
Sree S Kolli,1 Wasim Haidari,1 Steven R Feldman1–31Center for Dermatology Research, Department of Dermatology, Wake Forest School of Medicine, Winston-Salem, NC, USA; 2Department of Pathology, Wake Forest School of Medicine, Winston-Salem, NC, USA; 3Department of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, USA Kowalski et al describe various treatment approaches to achieve better outcomes in treatment-resistant prurigo nodularis in an article entitled, “Treatment-resistant prurigo nodularis: challenges and solutions.”1 Many excellent approaches are suggested, but the issue of nonadherence to topical therapies may be an overlooked issue commonly contributing to “treatment-resistance.” Often, in the face of “resistant” disease, patients may be prescribed more complicated or risky treatment regimens that make adherence even more difficult. Such strategies may not be the most effective ones when poor adherence underlies seemingly treatment-resistant prurigo nodularis.Treatment-resistance can often be overcome by measures that improve adherence. Even patients with severe, refractory atopic dermatitis respond rapidly to midpotency topical corticosteroids applied in the inpatient setting. Prurigo nodularis is often secondary to atopic dermatitis and psoriasis. In patients with atopic dermatitis or psoriasis that was “resistant” to topical corticosteroids, all patients treated with an easy to use topical corticosteroid spray improved rapidly when coupled with adherence promoting measures (telephone reminders, patient education and frequent office visits). Adherence to topical treatments is bad in the short-term and abysmal in the long-term.2–4 Perhaps one of the best approaches when faced with treatment-resistant disease is to simplify the treatment regimen and encourage good use of treatment, or better yet, bring patients in to assure the treatment is administered. View the original paper by Kowalski and colleagues